1993
DOI: 10.1038/sj.bdj.4808314
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the clinical performance of porcelain veneers

Abstract: A total of 315 porcelain labial veneers were fitted in 96 patients in two teaching hospitals, between July 1986 and October 1991, and were evaluated after a period of up to 63 months. During the evaluation period 53 (17%) restorations in 31 (32%) patients presented with a problem at review. Of these, 25 (8%) were of a minor nature and the veneer remained in use while 34 (11%) debonded or were removed. Increased problem and failure rates were associated with veneers placed on existing restorations, where tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 0 publications
1
51
1
3
Order By: Relevance
“…This relatively low survival rate for our functional design restorations in comparison with other studies (2,3), may be justified due to the design of the dental preparation that we used (extension of the restoration to the back side of the tooth, leaving a fine bevel). For this reason, and due to in vitro studies (14)(15)(16) Other authors (6,9) show less favorable results, likely related to incorrect cement application techniques. In the majority of the clinical studies on this type of restoration, the degree of patient satisfaction has been a factor taken into account.…”
Section: Analysis Of Mechanical Accidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relatively low survival rate for our functional design restorations in comparison with other studies (2,3), may be justified due to the design of the dental preparation that we used (extension of the restoration to the back side of the tooth, leaving a fine bevel). For this reason, and due to in vitro studies (14)(15)(16) Other authors (6,9) show less favorable results, likely related to incorrect cement application techniques. In the majority of the clinical studies on this type of restoration, the degree of patient satisfaction has been a factor taken into account.…”
Section: Analysis Of Mechanical Accidentsmentioning
confidence: 99%
“…(Fig. 1 and 2) As with any technique in the process of development, the use of porcelain laminate veneers requires both mid-term and long-term studies in order to verify their usefulness and allow them to continue to be used, establishing, reducing, or expanding their indications for the population (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These techniques have been used at the Prosthodontics and Occlusion Teaching Unit of the Department of Medicine and Dentistry of the University of Valencia since 1985, which has now treated a significant number of patients with porcelain laminate veneers in response to their esthetic demands.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a long-term follow-up 18 of veneers placed over a 10-year period shows a survival rate of 91% at 10.5 years (calculated with the Kaplan Meyer method). These excellent results may, amongst other things, reflect careful case selection, but it is worth noting that other authors, 5,13,19,20 have reported much higher rates of failure of between 7-14% over 2-5 years. Such studies suggest that the risk factors for veneer failure are:…”
Section: Historymentioning
confidence: 99%
“…Dunne and Millar reported that the incidence of such repairable defects (8%) was similar to the number of veneers requiring total replacement (11%). 5 It is useful to be aware of the above data when patients ask how long their proposed veneers are likely to last. It may also be prudent to warn them that although most (80-100%) 7 patients remain satisfied with the aesthetics, veneers are prone to marginal staining, the amount of which will vary from patient to patient.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation